Comparison of metabolic and heart rate responses to super slow vs. traditional resistance training - Hunter, G. R.; Seelhorst, D.; Snyder, S. (The Journal of Strength and Conditioning Research, 2003)
In order to compare the cardiovascular and energy expenditure demands of "Super Slow" (SST) and traditional (TT) resistance training 7 resistance-trained young men (24.3 ± 3.8 years) had energy expenditure (using indirect calorimetry) and heart rate evaluated during and for 15 minutes after a workout on separate days. Blood lactate levels were also evaluated before and after each intervention. Resting energy expenditure was evaluated in a fasted state using a ventilated canopy prior to any exercise stimulus and 21 to 22 hours after the SST and TT. O2 and average heart rate were both significantly higher during the TT than during the SST. The net O2 was also significantly higher during the 15 minutes recovery; however, average heart rate was not significantly different between the 2 groups. Total net energy expenditure from oxidative processes was 45% higher for the TT intervention (TT = 155 ± 28 kcal, and SST = 107 ± 20 kcal). The significant postexercise lactate difference was almost 2 times greater following the TT than after the SST (TT = 7.9 ± 1.7 mmol/L·min, and SST = 4.0 ± 2.0 mmol/L·min). Finally, adding the estimated energy expenditure of the blood lactate to the net energy expenditure from the O2 produced a significant difference that is over 48% greater for the TT intervention (TT = 172 ± 29 kcal/min, and SST = 116 ± 22 kcal/min). No significant repeated measures analysis main effect was found for either resting energy expenditure or respiratory exchange ratio. The metabolic and cardiovascular stimuli were low with SST. Traditional resistance training increases energy expenditure more than SST does and thus may be more beneficial for body weight control.